The Formation of Hui Ethnic Group in China in Yuang Dynasty: Diversity and Integration - Wei, Zhang; Iftikhar, Rukhsana (Annals of Human and Social Sciences, 2024)
China is known for its ethnic diversity. The emergence of the Hui community represents a unique phenomenon, characterized by the amalgamation of Islamic and Chinese cultures. Originating in the Tang Dynasty, the Hui community coalesced during the Yuan Dynasty, drawing from a diverse ethnic composition that encompassed various Islamic believers of the era. Predominantly comprised of Arabs, Persians, and Islamized Turkic groups, alongside a minority from South Asia, Southeast Asia, and Africa, as well as non-Islamic Azoreans, Jews, and Gypsies. The formation of the Hui during the Yuan Dynasty stemmed from the Mongol Western Expedition. This expedition facilitated the Hui formation through two principal means the enforced recruitment of soldiers and artisans by the Mongol army, and the reopening of the Silk Road, both overland and maritime, which facilitated the influx of Muslims, particularly of Arabian and Persian descent, into China. Furthermore, the vast expanse of the Yuan Dynasty, characterized by a multitude of ethnicities and relaxed ethnic policies, provided fertile ground for Hui formation. Concurrently, the notion of the Chinese nation embodied a concept of multi-ethnic assimilation, reflecting a pattern of pluralism within unity. This paper is an attempt to highlighlight the emergence of Hui community and its contribution to Chinese National life. Historical descriptive method is used to anaylized the data. The existence of Hui community revitalized the image of China that its economic progress is hidden in the unity in diversity.